4-(2-Hydroxybenzylideneamino)benzonitrile - Gong, Xing-Xuan (International Union of Crystallography, 2008)
The molecule of the title compound, C(14)H(10)N(2)O, is nearly planar. There is a strong intramolecular O—H⋯N hydrogen bond between the imine and hydroxy groups. The configuration with respect to the C=N double bond is anti (1E).